2012
DOI: 10.18352/jsi.285
|View full text |Cite
|
Sign up to set email alerts
|

Relationship quality and elder caregiver burden in India

Abstract: R a S h m I G u P Ta , V I J aya n K u m a R a P I L L a I , E I L E E n F. L E V y R E L aT I O n S h I P Q u a L I T y a n D E L D E R C a R E G I V E R B u R D E n I n I n D I aDr. Rashmi Gupta is Assistant Professor of Social Work at San Francisco State University. A B S T R A C T Relationship quality and elder caregiver burden in IndiaThe purpose of this study was to examine the psychosocial factors that contribute to burden among Asian Indian caregivers of the elderly in Allahabad, India. Within this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 50 publications
4
25
0
1
Order By: Relevance
“…Daughters-in-law were the caregivers in a significant number of households in our study, as found in studies in India and the Republic of Korea (21)(22)(23). Even among immigrants of Indian and Pakistani descent in the USA, daughters-in-law were the primary care givers, adhering to the cultural norms of their country of origin (24).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Daughters-in-law were the caregivers in a significant number of households in our study, as found in studies in India and the Republic of Korea (21)(22)(23). Even among immigrants of Indian and Pakistani descent in the USA, daughters-in-law were the primary care givers, adhering to the cultural norms of their country of origin (24).…”
Section: Discussionsupporting
confidence: 86%
“…This finding is supported by that of another study in Pakistan, in which male caregivers were more "stressed" (32); however, a study in India showed no difference in the stress levels of male and female caregivers (22). In Pakistan, caregiving is a "gender incongruent" role for men, who are the breadwinners and primarily fulfil responsibilities away from home.…”
Section: Discussionsupporting
confidence: 51%
“…In particular, the assessment of available resources to exercise care and coping strategies used by caregivers can influence the sense of capacity of the caregiver to meet the demands of activities, minimizing or enlarging the perception of burden 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, women are likely to report greater burden than men. 22 In present study, researcher found that women were majority of caregivers, but men perceived themselves as more burdened when faced with the challenge of caring for the elderly. In Myanmar culture, men who are the breadwinners and primarily fulfil responsibilities away from home.…”
Section: Discussionmentioning
confidence: 60%